Let -6-(-2x-y) = 0

open the bracket

-6+2x+y= 0

Adding 6 on both sides you will get

2x+y = 2

Now put any value of x in order to get the value of y like

Let x = 2 then

2(2)+y=6

4+y = 6

y=6-4

y=2

So if x=2 then y = 2

Let x = 4

2(4)+y=6

8+y=6

y=6-8

y=-2

So if x=4 then y = -2 and so on.

open the bracket

-6+2x+y= 0

Adding 6 on both sides you will get

2x+y = 2

Now put any value of x in order to get the value of y like

Let x = 2 then

2(2)+y=6

4+y = 6

y=6-4

y=2

So if x=2 then y = 2

Let x = 4

2(4)+y=6

8+y=6

y=6-8

y=-2

So if x=4 then y = -2 and so on.